Semeadura cruzada de soja em sistemas de manejo do solo - Menezes, Patricia Candida de (2013)
The challenge is to increase agricultural production while avoiding the opening of new areas. An alternative is to increase productivity through research and development of new technologies. The spatial arrangement of plants promoted by sowing crossed of soybeans may contribute to this increase. Given the above, we sought to evaluate the performance of soybean sown of crossed shape in tillage systems. The experimental design was a split plot, with the corresponding portions of the systems of tillage and subplots to sowing soybeans types. Each treatment had six replicates. The tillage systems were: conventional tillage, reduced tillage and no-tillage. The soybean sowing was carried out in a conventional manner, with parallel lines, and so crossed, where the sower went twice in the same area in perpendicular directions. The cultivar TMG 123 RR. Evaluations consisted in checking the severity of the rust, agronomic characteristics and operational performance of machines . The lower severity of rust was observed in the no-tillage and conventional tillage with conventional sowing. The sowing crossed of soybeans had higher plant height at flowering, maturation and first pod, grain yield in no-tillage system and demanded higher fuel consumption and energy demand.